Evaluating the relationship between ownership structure as corporate governance mechanism and accounting earnings management tools on the financial performance : A case of Egypt - Eman Fathi Ahmed Attia; Ibrahim Raslan Hegazy (Cairo : Eman Fathi Ahmed Attia, 2016)
As there has been an ongoing debates and conflict on whether the existence of institutional /family ownership eliminate or increase opportunistic accounting earnings management as well as financial performance. This study focuses on examining whether the internal mechanisms of corporate governance especially ownership structure (institutional/family shareholding) can control earnings management manipulations, which in turn enhance the firm performance in the listed companies in Egyptian stock exchange. This study focused on 49 listed companies including 392 observations whose shares are among Egypt{u2018}s 100 most actively traded shares (EGX100 price index) from the years (2006 to 2013) after excluding firms with insufficient data, banks and financial Institutions, and insurance companies from annual reports of Egyptian companies, Egyptian disclosure Books, and Egyptian financial statements. The study employs path analysis, and multi-group factor analysis using structural equation modelling (SEM) to test the strength and direction of the relation between ownership structure, discretionary accruals, and financial performance. In addition, the study applies advanced panel threshold regression estimation developed in 1999 by Hansen to determine institutional/ family threshold with earnings management and financial performance using ROA measure. This estimation procedure has the advantage of quantifying the threshold level of ownership structure as compared to the ad-hoc classification procedure of splitting the sample
Thesis (Ph.D.) - Cairo University - Faculty of Commerce - Department of Accounting
Issued also as CD
Keywords: Accounting earnings management; Family ownership; Institutional ownership